Hydrogen-rich bio-gas generation and optimization in relation to heavy metals immobilization during Pd-catalyzed supercritical water gasification of sludge. (15th December 2019) - Lin, Junhao; Sun, Shichang; Cui, Chongwei; Ma, Rui; Fang, Lin; Zhang, Peixin; Quan, Zonggang; Song, Xin; Yan, Jianglong; Luo, Juan
Abstract: This study aimed to investigate the relationship between the immobilization efficiency of heavy metals (HMs) and the generation of bio-gas under different catalyzing conditions during the supercritical water gasification of sludge. Results showed that catalysts could promote the decomposition of organic matters to improve the yield of bio-gas and the order of the catalysts in terms of H2 selectivity was Pd > CaO > AlCl3 . Pd catalyst not only promoted the generation of hydrogen-rich bio-gas but also enhanced the immobilization efficiency of HMs. This was because the Pd catalyst facilitate the steam reforming reaction of the high-molecular-weight organic matters while promoting the combination of HMs with mineral components to form stable crystalline compounds. When the addition amount of Pd catalyst was 10 wt %, the yield of hydrogen-rich bio-gas increased from 35.74 wt% to 46.88 wt%, and the leaching concentration of Zn, Cu, and Cr decreased significantly to 1.22 mg/L, 0.55 mg/L and 0.38 mg/L, respectively. In addition, rational adjustment of addition amount of catalyst could optimize the specific surface area of the bio-char to enhance the physical adsorption of HMs via affecting the process of bio-gas generation. Graphical abstract: Image 1 Highlights: Decomposition of C–C and C–H bonds in organics increased the yield of H2 in SCWG. Pd catalyst facilitates the steam reforming of organic matters to generate H2 . Adjusting the production of bio-gas promotes the immobilization of HMs in bio-char. The formation of pore in bio-char contributes to the immobilization of Zn and Cu.